An exploration of the financial practices of tribal communities in Jhabua, India. Issue 6 (18th August 2017) - Guha, Samapti; Patel, Hemangi; Parekh, Nadiya
ABSTRACT: Tribal communities of India have been facing financial challenges for many years, and these have increased alongside commercialisation led by industrialisation. The major reason for this is that tribal communities are neglected by the state, which has had a negative impact on their livelihoods and financial status. The state has made some attempts to promote these communities, but these have been unsuccessful. Against this background, this article explores the financial practices of tribal communities in Jhabua district of Madhya Pradesh, India and presents a microfinance model which could be suitable in the Jhabua context.